Thermometry: from sensitive material to thermoelectric thermotransducer - Stadnyk, Bohdan; Skoropad, Pylyp; Yatsyshyn, Svyatoslav (Видавництво Львівської політехніки, 2005)
The hard operation conditions of temperature thermotransducers which involve their thermal cycling require special attention to the study of processes occurring in structural elements, in particular in thermometric materials. Operation impacts cause the drift of thermometric characteristics due to the influence of the few factors main of which seem to be the thermo structural stresses. Therefore, different kinds of sensitive elements were studied. Since traditional polycrystalline thermoelectrodes of thermocouples are inherent in the well-known drawback linked with recrystallization, there were investigated the liquid metals as the thermometric substances, melts, single-crystal materials, and metallic glasses. The need for metal glasses application in thermometry is substantiated, which allows eliminating thermally activated gradients of internal stresses in thermocouples ensuring high reproducibility and low drift of their thermo-EMF comparing to traditional materials. The analysis of sources of the instability of thermocouples’ drift is carried out. It demonstrates the density of heat and electric flows in stressed thermoelectrodes depends not only on temperature and electric potential gradient but also on the stresses’ gradient. This causes the dependence of thermometric parameters of both poly- and single-crystal substance of thermoelectrodes on the value and nature of stresses occurring within the operation cycle.
Keywords: Temperature; Thermo-EMP; Thermocouple; Amorphous metal alloy; Measurement error